Canada needs its "New Approach" to streamline digital rulemaking - Michel Girard (Centre for International Governance Innovation (CIGI), 2023)
Canada's current approach to rulemaking is not keeping pace with the deployment of new digital technologies. This paper proposes to modernize the Statutory Instruments Act to bridge that gap, suggesting that mandatory standards, technical specifications and conformity assessment programs should be recognized as statutory instruments alongside regulations. This borrows from the European Union's "New Approach" established in 1985, whereby regulators can request that EU standards bodies develop mandatory standards as a compliance mechanism to laws, even while legislation is being drafted. Streamlining rulemaking is essential to help manage the harms associated with digital technologies as soon as possible after they are commercialized.
Keywords: 330